Analysis of folic acid in white rice by ultra-fast liquid chromatography (2019)
The method of analysis was standardized, and the folic acid content was determined in samples of fortified white rice (Z, G and D) and unfortified (E and O). The analysis was performed in triplicate in samples of 2.0000 g, hydrolysis was performed with phosphate buffer pH 8.82 for one hour and then lowered to pH 7.00 for enzymatic treatment with takadiastase at 65°C. The extracts were filtered by gravity, purified with nylon syringe filters and ion exchange cartridges (solid phase extraction using strong anion exchange cartridges). The concentration in mg folic acid/kg of rice, in each extract was determined by ultrafast liquid chromatography, with average values for Lot1 of the fortified rice samples, of 44.03, 51.95, 38.08, and unfortified samples of 31.51 and 21.94, and with respect to Lot2 of 41.26, 41.27, 34.54 for fortified ones and 24.92 and 20.94 for non-fortified ones, respectively. The concentration of folic acid obtained by filtration through syringe filters was higher than in the extracts purified by solid phase extraction using strong anion exchange cartridges, evidencing loss of the analyte. The recovery of folic acid in the samples doped and purified by syringe filters was around 65.00%, while by solid phase extraction using strong anion exchange cartridges 43.00%. There is evidence of variation in the folic acid content between different batches of rice of the same brand.